2016
DOI: 10.1364/ol.41.004787
|View full text |Cite
|
Sign up to set email alerts
|

Optical encryption with protection against Dirac delta and plain signal attacks

Abstract: This Letter proposes an optical encryption technique that disguises the information with modular arithmetic concepts and time-varying noise components that are unknown to the receiver. Optical encryption systems that use these techniques produce a nondeterministic system response, as well as noise like image data that can easily be generated with ordinary spatial light modulators. The principle of this technique is demonstrated for the double random phase encoding (DRPE) method. The conventional DRPE method ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…For example, the nonlinear modifications previously mentioned [16,17], not only reduces the noise over the recovered data, but also increases the security against to chosen plaintext attacks and cyphertextonly attacks. Other modifications, like the use of cryptographic salting [34] and phase only encryption [35,36] avoid known ciphertext attacks.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the nonlinear modifications previously mentioned [16,17], not only reduces the noise over the recovered data, but also increases the security against to chosen plaintext attacks and cyphertextonly attacks. Other modifications, like the use of cryptographic salting [34] and phase only encryption [35,36] avoid known ciphertext attacks.…”
Section: Introductionmentioning
confidence: 99%
“…Another important attack that must be analyzed is the chosen plaintext attack (CPA) [12,13]. In this case, an intruder with access to the cryptosystem encrypts a Dirac delta function.…”
Section: Resistance To Attacksmentioning
confidence: 99%
“…The ongoing research in the optical encryption field led to the discovery of vulnerabilities in the DRPE based schemes [12][13][14][15][16][17][18]. In particular, it was found that certain techniques could be implemented to overcome the security of DRPE cryptosystems.…”
Section: Introductionmentioning
confidence: 99%
“…The first of these categories of attacks is the chosen plaintext attack (CPA), where the attacker has full access to the cryptosystem, and can introduce specially tailored plaintexts to be encrypted in order to deduce the encryption key. This was the first kind of attack demonstrated against the DRPE scheme [6]; however, several methods have been proposed to thwart them [7,8]. In practice, most actual encryption systems, digital or optical, are known to be vulnerable if the attacker has full access to the encryption machine.…”
Section: Introductionmentioning
confidence: 99%